CRITICAL THINKING SKILLS FOR CHINESE TEACHERS: A STUDY OF MATHEMATICS TEACHERS’ PERCEPTIONS: Received: 10th January 2023; Revised: 7th June 2023, 14th June 2023; Accepted: 22nd June 2023 - Liu, Wei (PUPIL: International Journal of Teaching, Education and Learning, 2023)
Critical thinking is a vital skill that promotes students’ learning, enhances their creativity to solve problems, encourages them to seek new strategies and develops their thinking to a higher level. However, students cannot develop critical thinking by themselves, they need teachers’ support and guidance. The aim of the research is to explore how Chinese mathematics teachers define critical thinking, and how their gender, teaching experiences and perceptions of critical thinking affect their mathematics class. Quantitative and qualitative methods were applied in the study. Data collected were analysed by deploying the statistics of mean, standard deviation, and Pearson’s analysis at a 5% level of significance. Based on this paper, results revealed that gender and teaching experience are not significant variables but teaching experience and culture influence teachers’ confidence and behaviour while teaching critical thinking. This study provided opportunities for future research, particularly in the area of closing the gap in mathematics teachers’ perception of critical thinking between China and Western countries, and how to support students develop critical thinking skills in their daily learning.